2008
DOI: 10.1007/s11064-008-9727-4
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Inhibits Protein Kinase Cγ and Calcium/Calmodulin Dependent Protein Kinase II-α Translocation to Synaptic Membranes in Ischemic Mice Brains

Abstract: Volatile anesthetics isoflurane possibly improves the ischemic brain injury. However, its molecular actions are still unclear. In ischemia, protein kinase C (PKC)gamma and calcium/calmodulin dependent protein kinase II (CaMKII)-alpha are persistently translocated from cytosol to cell membranes, and diminish these translocation suggested to be neuroprotective. We thus tested a hypothesis that isoflurane inhibits PKCgamma and CaMKII-alpha translocation after ischemic brain insults. C57Bl/6J male mice were made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The reasons for these different findings are not known. However, consistent with our findings, it has been proposed in a recent study that inhibition of CaMKII trafficking to the plasma membrane, a possible activation process for CaMKII, is a mechanism for isoflurane-induced neuroprotection (Matsumoto et al, 2008). Interestingly, there is no report on the role of IP3 receptor-calcium-CaMKII pathway in isoflurane postconditioning-induced neuroprotection.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for these different findings are not known. However, consistent with our findings, it has been proposed in a recent study that inhibition of CaMKII trafficking to the plasma membrane, a possible activation process for CaMKII, is a mechanism for isoflurane-induced neuroprotection (Matsumoto et al, 2008). Interestingly, there is no report on the role of IP3 receptor-calcium-CaMKII pathway in isoflurane postconditioning-induced neuroprotection.…”
Section: Discussionsupporting
confidence: 93%
“…Within the brain, PKCγ levels are most abundant in the cerebellum, hippocampus and cerebral cortex, where notable neuronal plasticity occurs (33,34). Recently, Matsumoto et al demonstrated that the PKCγ expression was significantly increased following TBI in rats (35). Nevertheless, to the best of our knowledge, no studies have examined the potential for BBG to regulate the expression of PKCγ in neurons in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of cPKCc membrane translocation by its inhibitor can inhibit the increment in lactate dehydrogenase (LDH) leakage induced by 20-min. OGD treatment and decrease the decapitation-induced ischaemic brain injury of C57Bl/6J mice [5,11]. The different effects of cPKCc may be attributable to the use of different species, models, protocols, measured end-points and inhibitors.…”
Section: Introductionmentioning
confidence: 99%